Associate Professor Dr. Hazrulrizawati produces bone treatment products through deer antlers - Hafizatulazlin, Abdul Aziz (2023)
PAYA BESAR, 27 December 2022 – Researcher and lecturer of the Faculty of Industrial Science and Technology (FSTI), Universiti Malaysia Pahang (UMP), Associate Professor Dr. Hazrulrizawati Abd Hamid, 40, has created a product that could be used for bone treatment.